Réponses

  • Omnes
  • Modérateur confirmé
2014-03-14T22:58:39+01:00
Salut,

I = 49/12 * (3/7 + 3/14)
I = 49/12 * (6/14 + 3/14)
I = 49/12 * 9/14
I = 7/4 * 3/2
I = 21/8


I* = 49/12 * (3/7 + 3/4)
I* = 49/12 * 3/7 + 49/12 * 3/14
I* = 7/4 * 1/1 + 7/4 * 1 /2
I* = 7/4 + 7/8
I* = 21/8

J = 18*(4/3 - 5/6)
J = 18*(8/6 - 5/6)
J = 18*(3/6) = 18*(1/2)
J = 9


J* = 18 * 4/3 + 18*(-5/6)
J* = 6 * 4  + 3 * (-5)
J* = 24 - 15
J* = 9

K = 3/8 * 1/3 + 3/16 * 1/3
K = 1/8 + 1/16
K = 2/16 + 1/16 = 3/16

K* = 1/3(3/8 + 3/16)
K * = 1/3 * (6/16 + 3/16)
K* = 1/3 * 9/16
K* = 1 * 3/16
K* = 3/16

Bonne soirée !
Merci tu est grave sympa a tu biens respecter les consignes ?